Systematic literature review on ethical consideration in multimedia professional practices - Shahbodin, Faaizah; Che Ku Mohd, Che Ku Nuraini; Rahim, Nur Raidah; Chandini Pendit, Ulka; Dewi, Laksmi; Mohd Kasim, Helmi (Little Lion Scientific Islamabad Pakistan, 2024)
The rapid advancement in technologies provide the different method of presenting information to the audience in multimedia. However, this leads to the needs to review the current ethics challenges faced by the multimedia professional. This research aims to give insight in the ethical consideration including the challenges faced by the professionals and provide a guideline in ethic decision making by having a systematic literature review. Privacy issues, balance between realism and addiction and truthfulness of information are the ethical challenges faced by the multimedia professionals. Cooperation among the community and involvement of the audience in the development process are the guideline provided to minimize the risk of the ethics issues faced by them.